2017
DOI: 10.1016/j.idcr.2017.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Toxic shock syndrome due to community-acquired methicillin-resistant Staphylococcus aureus infection: Two case reports and a literature review in Japan

Abstract: Community-acquired methicillin-resistant Staphylococcus aureus has been spreading worldwide, including in Japan. However, few cases of toxic shock syndrome caused by Community-acquired methicillin-resistant Staphylococcus aureus have been reported in Japan. We report 2 cases, in middle-aged women, of toxic shock syndrome due to Community-acquired methicillin-resistant Staphylococcus aureus via a vaginal portal of entry. The first patient had used a tampon and the second patient had vaginitis due to a cleft nar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The kidney is one of the most affected organs during multiple organ failure associated with sepsis, 29 and mTSS places renal function in dire jeopardy. 30 In an early report, full-swing acute renal failure was observed in all nine fatal cases of mTSS. 31 Unlike IgA-dominant infection-associated GN, S. aureus exotoxin rather than enterotoxin is responsible for mTSS and associated multiple organ failure.…”
Section: Discussionmentioning
confidence: 95%
“…The kidney is one of the most affected organs during multiple organ failure associated with sepsis, 29 and mTSS places renal function in dire jeopardy. 30 In an early report, full-swing acute renal failure was observed in all nine fatal cases of mTSS. 31 Unlike IgA-dominant infection-associated GN, S. aureus exotoxin rather than enterotoxin is responsible for mTSS and associated multiple organ failure.…”
Section: Discussionmentioning
confidence: 95%
“…IL-6 is a cytokine produced at high levels as a result of SAg activity ( 22 ). LDH, found in almost every cell in the body, is released into the systemic circulation as a result of tissue injury including the cytotoxic effects of cytokine storms ( 23 25 ). On average, both IL-6 and LDH levels in rabbits infected with S. aureus expressing toxoids were not significantly different from those in rabbits infected with S. aureus SEC KO ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MRSA can produce many exotoxins such as TSST-1 and α-hemolysin which were associated with a severe illness that includes shock and multiple organ failure and is called toxic shock syndrome. [ 28 29 ] Approximately 20% and 5% of MRSA isolates possess the genes encoding TSST-1, and α-hemolysin, respectively. However, the result of the current study showed that 16 isolates (64%) and 4 isolates (16.6%) were positive for the TSST-1 and α-hemolysin gene, respectively.…”
Section: Discussionmentioning
confidence: 99%